Total leukosit dan diferensial leukosit darah ayam broiler akibat penggunaan tepung onggok fermentasi rhizopus oryzae pada ransum - Dian Purnomo; Sugiharto Sugiharto; Isroli Isroli (Faculty of Animal Science, Universitas Brawijaya, 2015)
The aim of the present study was to determine the effect of cassava pulp fermented with Rhizopus oryzae on the total leucocyte and differential leucocyte and its influence on the health of broiler chickens. The study was conducted in July-September 2015. The material used was 275 DOC of broiler with average of initial weight 55 g. Ration ingredient used were corn, rice bran, soybean meal, fish meal, poultry meat meal and fermented cassava pulp. The experiment used a completely randomized design (CRD) comprised of 5 treatments and 5 replications. Treatment ration consist of T0 (control ration), T1 (8% cassava pulp without fermentation), T2 (8% cassava pulp fermented with Rhizopus oryzae), T3 (16% cassava pulp fermented with Rhizopus oryzae) and T4 (24% cassava pulp fermented with Rhizopus oryzae). The result of the study showed that there was no influence among treatments (P>0,05) of the use of cassava pulp fermented with Rhizopus oryzae in ration to total leucocyte and differential leucocycte. It is concluded that cassava pulp fermented with Rhizopus oryzae in ration is potential to substitute the use of corn in ration without compromising the health and amount of total leucocyte and differential leucocyte. Keywords: Rhizopus oryzae, leuycocyte, differential leucocyte, broiler